Alcohol and substance-induced disorder treatment cases in mental health and addiction treatment facilities from 2013 to 2022: A descriptive study - Orrin D. Ware (PLOS Mental Health, 2026)
Substance use disorders may arise when individuals use substances to cope with adverse mental health symptoms. Conversely, mental health symptoms can develop because of substance use, a category of conditions called substance-induced disorders. This study used two United States-based datasets, the Mental Health Client-Level Data and the Treatment Episode Data Set Admissions, to summarize the number of cases with “alcohol-induced disorders” and “substance-induced disorders” from both mental health and substance use disorder treatment programs from 2013 to 2022. The primary study aim was to identify the percentage of cases with alcohol-induced disorders or substance-induced disorders in these treatment settings. Among all mental health disorder treatment cases, those with an alcohol or substance-induced disorder totaled N = 439,932, making up 0.7% of total cases over the analytic period. During the same period, alcohol or substance-induced disorders totaled N = 459,817, accounting for approximately 2.7% of all substance use disorder treatment cases. The majority (79%) of cases with an alcohol-induced disorder in substance use disorder treatment were identified as reporting alcohol use, with 68% having alcohol listed as their primary substance. Heroin and other opiates and synthetics accounted for the primary substance among 28.8% of cases with a substance-induced disorder in the substance use disorder treatment data. Approximately 1 in 3 cases with an alcohol-induced disorder and 1 in 4 cases with a substance-induced disorder had a depressive disorder diagnosis in mental health treatment. When considering the primary diagnosis, approximately 1 in 4 cases with an alcohol-induced disorder and 15% of cases with a substance-induced disorder had a depressive disorder as the primary diagnosis in mental health treatment. Substance-induced disorders are a significant public health concern, and more research is needed to better understand the clinical needs of this population.